2022
DOI: 10.3390/ijerph19052725
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Teacher Burnout and the Effects of Resource Factors: A Latent Transition Perspective

Abstract: To better understand burnout and its development, researchers have shown an increasing interest in recent years in identifying different profiles of burnout and its development process. However, there have been few longitudinal studies on the profile and development of teacher burnout. This study used a person-centred approach to explore the profiles of teacher burnout, transition probabilities and the associations between these aspects and resource factors. Data were collected from 3743 primary school teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
2
0
2
Order By: Relevance
“…Los resultados obtenidos confirman varias de las hipótesis inicialmente establecidas. Así, de conformidad con la primera hipótesis (H1), y en línea con otros estudios (Freire et al, 2020;Li et al, 2019;Molero et al, 2019;Peng et al, 2019;Skaalvik y Skaalvik, 2020;Xie et al, 2022), tanto el capital psicológico como la satisfacción laboral docente se mostraron como predictores directos negativos del burnout, con un importante tamaño del efecto. De acuerdo con el Modelo DRL (Schaufeli, 2017), la disponibilidad de buenos recursos personales, incluso en entornos altamente demandantes, reduciría significativamente la probabilidad de experimentar estados psicopatológicos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados obtenidos confirman varias de las hipótesis inicialmente establecidas. Así, de conformidad con la primera hipótesis (H1), y en línea con otros estudios (Freire et al, 2020;Li et al, 2019;Molero et al, 2019;Peng et al, 2019;Skaalvik y Skaalvik, 2020;Xie et al, 2022), tanto el capital psicológico como la satisfacción laboral docente se mostraron como predictores directos negativos del burnout, con un importante tamaño del efecto. De acuerdo con el Modelo DRL (Schaufeli, 2017), la disponibilidad de buenos recursos personales, incluso en entornos altamente demandantes, reduciría significativamente la probabilidad de experimentar estados psicopatológicos.…”
Section: Discussionunclassified
“…El capital psicológico se define como un estado psicológico individual positivo fruto de la conjugación de cuatro recursos (Luthans et al, 2015): (a) eficacia (confiar en la capacidad para asumir y realizar los esfuerzos necesarios para tener éxito en tareas desafiantes); (b) esperanza (perseverar en los objetivos y, cuando sea necesario, reorientarlos para alcanzar el éxito; (c) optimismo (tendencia a realizar atribuciones positivas sobre el rendimiento actual y a generar expectativas positivas sobre el éxito futuro); y (d) resiliencia (recuperarse y salir fortalecido de las adversidades para alcanzar los objetivos deseados). Varios estudios muestran que el capital psicológico se relaciona con bajos niveles de burnout en docentes de todas las etapas educativas (Freire et al, 2020;Li et al, 2019;Peng et al, 2019;Xie et al, 2022). Estos hallazgos suponen un refrendo empírico del modelo DRL, al evidenciar que el capital psicológico se erige en un recurso personal eficaz para reducir la vulnerabilidad al burnout en un contexto laboral altamente demandante (Schaufeli, 2017).…”
Section: Capital Psicológico Satisfacción Laboral Y Burnoutunclassified
“…Therefore, longitudinal relations between burnout, self-efficacy, and writing conceptions remain unknown, as does the direction of their effects. Future research can use latent transition analysis (LTA) to explore the probabilities of transitions from one burnout profile to another over time, like what have been conducted among teachers (Xie et al, 2022), and corresponding changes of writing conceptions. The second limitation is that the sample size was smaller than 200, which is below the typically recommended number for BLRT and BIC to generate identification with ideal correct rate (Nylund et al, 2007).…”
Section: Limitations Direction Of Future Research and Practical Impli...mentioning
confidence: 99%
“…A study by Xie, Huang, Ke, Wang and Wang (2022) have showed an increased interest in recent years in identifying various burnout development profiles to better understand burnout and its progression. However, there have been few longitudinal studies tracking the characteristics and progression of burnout among educators.…”
Section: Empirical Reviewmentioning
confidence: 99%